Central Bank Reforms in the Baltics, Russia, and the Other Countries of the Former Soviet Union - Knight, Malcolm (Occasional Papers; Occasional Paper ;, 1998)
Since 1991, the 15 countries under review - have to varying degrees, been pursuing reforms whose broad objectives have been to achieve market-based determination of interest rates and exchange rates, manage banking system liquidity through market operations with indirect instruments, and provide the institutional underpinnings for the design and implementation of macroeconomic stabilization and structural reform programs supported by the IMF. This study reviews the experience under these programs and the economic developments in the countries that undertook them.